PENGARUH PELAYANAN PRIMA, KEPUASAN PELANGGAN DAN LOKASI TERHADAP LOYALITAS PELANGGAN - Chusnah, Chusnah; Syukhul, Muhammad (Kinerja, 2022)
This study aims to determine the effect of excellent service, customer satisfaction and location, on customer loyalty at PT. Binajasa Abadi Karya. This study uses primary data, by distributing questionnaires through the G-form. The research sample is 82 companies that use services or are tenants at PT. Binajasa Abadi Karya. The data analysis method used multiple linear regression. The results showed that partially excellent service, customer satisfaction and location had a positive and significant effect on customer loyalty. Results of F-test showed that excellent service, customer satisfaction and location simutaneously affect customer loyalty, with an adjusted R-square value of 46.1%.